The Influence of using Hangman game on the seventh graders’ vocabulary mastery - Dewi Sri Kuning; Rohaina Rohaina (UAD TEFL International Conference)
Vocabulary is an important component in learning a language. Vocabulary is used to communicate to each other through listening, writing, speaking, and reading. These skills are closely related to vocabulary mastery. However, students have difficulties in understanding the vocabularies from their reading or listening activities. This research belongs to quantitative study using quasi experimental of nonequivalent control group design to find out the influence of using Hangman game on the seventh graders’ vocabulary mastery. The data were collected through a multiple-choice test. The hypothesis is tested using t-test. From the calculation of t-test, it was found that tobserved = 2.7, with df = 30+29-2 = 57 in ttable = 2.0, because tobserved ≥ ttable or 2.7 ≥ 2.0. Therefore, it can be concluded H0 is rejected, while Ha is accepted. In other words, “Hangman game influences the seventh graders’ vocabulary mastery.”